Pengaruh Jus Rumput Laut (Eucheuma Sp) terhadap Peningkatan Kadar Hb Ibu Hamil Trimester I dengan Anemia - Mawaddah, Sofia; Adawiyah, Rabiatul (Jurnal Kesehatan, 2021)
The effect of anemia in pregnancy is not good for the mother, both during pregnancy, childbirth, and in the puerperium. One of the foods that contain iron is seaweed. Seaweed (Eucheuma sp) is one of the foodstuffs that contain several intermediate compounds needed in the synthesis of hemoglobin such as iron, protein, and vitamin B complex. The purpose of this study was to determine the effect of seaweed juice (Eucheuma sp) on increasing hemoglobin levels of pregnant women in the first trimester of anemia. This study was a pre-experimental study with a one-group pretest-posttest design with a sample of 30 pregnant women in the first trimester who met the inclusion criteria of the study. Researchers measured Hb levels before after being given seaweed juice, the statistical test used was the Paired T-Test test, p-value= 0,000. The conclusion from this study was that seaweed juice could increase Hb levels in first-trimester pregnant women with anemia.